2017
DOI: 10.4102/curationis.v40i1.1698
|View full text |Cite
|
Sign up to set email alerts
|

Lived experiences of parents of premature babies in the intensive care unit in a private hospital in Johannesburg, South Africa

Abstract: BackgroundMany of the 15 million premature babies born worldwide every year survive because of advanced medical interventions. Their parents have intense experiences when their babies are in the intensive care unit (ICU), and these have an impact on their thoughts, feelings and relationships, including their relationships with their premature babies.ObjectivesThe aim of the study was to explore and describe the lived experiences of parents of premature babies in an ICU.MethodResearch design was qualitative, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 43 publications
(45 reference statements)
3
25
0
12
Order By: Relevance
“…This necessitates the involvement of significant others like parents-in-law and husbands during information and counselling sessions for informed decisionmaking. This is in line with other studies that report on addressing fear, anxiety, anger [26], guilt [27], worry and lived experiences [28] between caregivers and their significant others for informed shared decision-making.…”
Section: Discussionsupporting
confidence: 91%
“…This necessitates the involvement of significant others like parents-in-law and husbands during information and counselling sessions for informed decisionmaking. This is in line with other studies that report on addressing fear, anxiety, anger [26], guilt [27], worry and lived experiences [28] between caregivers and their significant others for informed shared decision-making.…”
Section: Discussionsupporting
confidence: 91%
“…Nurses working in such units need to acknowledge the challenges experienced by mothers and plan effective care to meet the needs of both baby and mother. Provision of timely and comprehensive information to mothers on the condition, treatment and care of their babies (Gaucher & Payot, ; Steyn et al, ) could relieve mothers' anxiety and also promote confidence in the healthcare team (Arzani, Valizadeh, Zamanzadeh, & Mohammadi, ; Williams et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Steyn, Poggenpoel, & Myburgh, ; Taylor, ; Wigert, Johansson, Berg, & Hellstrom, ) described the experiences of mothers with preterm babies in settings where mothers are not accommodated in the hospital premises but can have access to their babies. There is lack of information on the experiences of mothers in a hospital environment that serves as a mother and baby unit (MBU).…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of access to specialized neonatal care units (NCUs) for sick and small newborns is one of the global priorities to reduce neonatal mortality [1]. Despite the tremendous bene ts of NCUs in achieving better neonatal health outcomes, studies exploring experience of parents in NCUs have shown it to be a stressful experience for families [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…While there is a large body of literature regarding parental experience in NCUs in western countries, very little is known in Sub-Saharan Africa [9,10]. A small number of studies in South Africa showed that parents often experience negative emotional feelings and various challenges in NCUs [8,11]. Many parents expressed depressive symptoms and inability to bond with their newborns [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%